1992
DOI: 10.1002/ps.2780340311
|View full text |Cite
|
Sign up to set email alerts
|

Diflubenzuron and oogenesis in the codling moth, Cydia pomonella (L.)

Abstract: Diflubenzuron, topically applied (0·5 μg insect−‐1) to Cydia pomonella (L.) at pupal ecdysis disturbed growth and development of oocytes. It delayed the adult ecdysis and caused a decrease in both thickness of the follicular epithelium and the size of the basal oocyte during the pupal development. On the other hand, the size of basal oocytes, the protein content per ovary and the number of oocytes per ovary recorded in newly emerged adults were significantly reduced after diflubenzuron treatment. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
3
30
1
2
Order By: Relevance
“…1974 ; Soltani et al . 1984a ; Mohsen & Mehdi 1989; Soltani & Soltani‐Mazouni 1992; Soltani et al . 1996 ).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…1974 ; Soltani et al . 1984a ; Mohsen & Mehdi 1989; Soltani & Soltani‐Mazouni 1992; Soltani et al . 1996 ).…”
Section: Discussionunclassified
“…Moreover, treatment resulted also in an increase of the duration of development of the larval instars tested, confirming the effects induced by this class of insecticides ( Soltani et al . 1989 ; Soltani & Soltani‐Mazouni 1992; Soltani et al . 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecdysteroid titre was observed in 7 day-old pupae to 4 day-old adult female ovaries. Soltani and Mazouni (1997) reported ecdysone levels that when ovaries from 4 day-old females of mealworm, i.e. at the end of vitellogenesis were cultured in media supplemented with diflubezuron, preliminary data indicated that ovarian amounts of ecdysteroids, as measured in vivo, changed during vitellogenesis of the T. molitor in a characteristic way.…”
Section: Effects On Ecdysteroid Titres Of Ovaries and Testesmentioning
confidence: 97%
“…Thereafter, this procedure was routinely applied for evaluation of DFB residues in different organs and tissues from several insect pests [23][24][25], and also to study DFB degradation in seawater [26]. These toxicity and degradation studies were limited almost exclusively to acute exposure of DFB.…”
Section: Introductionmentioning
confidence: 99%